Cerrahi Hastasının Hemşirelik Bakımında Güncel Yaklaşımlar-Güz - Özbaş, Nilgün; Usta, Esra; Karazeybek, Ebru; Güner, Yasemin; Özcan, Tuğba; Serpici, Ayşe; Demirci Güngördü, Nuray; Koçan, Sema; Bulut, Enes; Dizdar, Ebru; Çoban, Niran; Ertürk Yavuz, Melek; et al. (Academician Publishing Book DOI Portal, 2024)
-